How School Leaders Can Use Formative Assessment Strategies to Enhance School Climate - Bond, John (International Dialogues on Education Journal, 2017)
Formative assessment is widely implemented in the classroom to provide both teachers and students timely feedback about learning. A growing body of applications of formative practice has emerged over the last few decades that is based upon research. This is a highly successful approach that has the potential to serve school leaders and enhance school climate and culture. In this manuscript how school leaders can apply formative assessment concepts and strategies to assess and improve working relationships is examined. Specific strategies that principals, teacher leaders, and superintendents can use are reviewed. Discussed are the reflective practice that is facilitated by use of such strategies and how this experience is received by the constituencies a leader serves.